The Vulnerable Fishing Cat Prionailurus viverrinus from Wonorejo Mangroves, Surabaya, Indonesia Based on Morphology and Molecular Data - Sunu Kuntjoro; Dwi Anggorowati Rahayu; Widowati Budijastuti; Winarsih Winarsih (UIN Sunan Gunung Djati Bandung, 2023)
The fishing cat (Prionailurus viverrinus) is a protected animal. Currently, the population in nature is declining due to over-fishing and changes in environmental quality. The existence of this fishing cat is an interesting finding that must be immediately studied at the morphological and genetic levels for certainty of its species. This study aimed to identify fishing cat from Wonorejo Mangroves, based on morphology and Cyt b genes analysis. The results of Cyt b identification obtained a DNA sequence length of 398 bp with a similarity value of the five Prionailurus sp. samples between 96.75 to 98.97%. The identification using molecular data consisted of five variations of nucleotide bases, and the average value of the genetic distance with the ingroup was 1.0%., The Cyt b DNA markers analysis succesfully identified fishing cat from Wonorejo Mangroves as Prionailurus viverrinus.